Hubungan antara Asam Traneksamat dan Insiden Kejang pada Pasien dengan Perdarahan Subaraknoid - Dian Rizki Fitria; I Wayan Widyantara (MEDICINUS, 2026)
Background: Subarachnoid hemorrhage (SAH) accounts for 2–7% of all strokes but contributes disproportionately to morbidity and mortality due to severe complications such as rebleeding, delayed cerebral ischemia, and seizures.Tranexamic acid (TXA) is used to prevent rebleeding in SAH; however, the association between TXA use and seizure riskremains controversial.Methods: A systematic literature review was conducted to identify clinical studies reporting seizure incidence in adult patients with SAH who received TXA. Randomized controlled trials, cohort and case-control studies were included as primary studies. Data were synthesized narratively, with limited quantitative analysis performed when feasible.Results: Five studies met the inclusion criteria. Most studies demonstrated a signal toward an increased risk of seizuresor adverse neurological effects in patients receiving TXA compared with control groups. Safety data suggests that seizure risk tends to increase with total TXA doses exceeding 2 g per day, whereas low-to-moderate doses administered for a shortduration were not consistently associated with an increased incidence of seizures.Conclusion: TXA use in patients with SAH may be associated with an increased risk of seizures, particularly at higher doses. Although TXA provides benefits in reducing rebleeding, careful risk–benefit assessment and appropriate dose selection are essential, especially in patients with neurological vulnerability.